An Emotional Agent for Moral Impairment Rehabilitation in TBI Patients - Ceccaldi, Eleonora; Damiano, Rossana; Battaglino, Cristina; Galetto, Valentina; Zettin, Marina (Frontiers in Psychology, 2020)
The ability to identify the emotions of others is a key component of what is known as social cognition. Narratives exploit this mechanism to create an emotional bond with the characters and to maintain the engagement of the audience throughout the story. In this paper, we describe a case study in emotion understanding in stories that leverages a computational agent to explore emotion impairment in a group of traumatic brain injured people. We focus on moral emotions, in order to address the differences in moral functioning that characterize traumatic brain injured patients. By comparing the understanding of the moral and emotional aspects of the agent’s behavior in traumatic brain injured patients and in a control group of neurologically healthy subjects, we observed slight, yet meaningful differences between the two groups. We describe the test methodology and results, discussing their implications for the design of rehabilitation applications that leverage virtual agents